Comprehensive Planning for Growth Management in Florida - Roy R. Carriker (EDIS)
FE642, a 6-page fact sheet by Roy R. Carriker, is intended to serve as a primer to the subject of comprehensive planning in Florida, with the hope that it will be useful to residents who wish to play a greater role in community affairs. Published July 2006.